Design, Synthesis, and In Vitro, In Silico and In Cellulo Evaluation of New Pyrimidine and Pyridine Amide and Carbamate Derivatives as Multi-Functional Cholinesterase Inhibitors - Martina Bortolami; Fabiana Pandolfi; Valeria Tudino; Antonella Messore; Valentina Noemi Madia; Daniela De Vita; Roberto Di Santo; Roberta Costi; Isabella Romeo; Stefano Alcaro; Marisa Colone; Annarita Stringaro; et al. (MDPI AG, 2022)
Alzheimer disease is an age-linked neurodegenerative disorder representing one of the greatest medical care challenges of our century. Several drugs are useful in ameliorating the symptoms, even if none could stop or reverse disease progression. The standard approach is represented by the cholinesterase inhibitors (ChEIs) that restore the levels of acetylcholine (ACh) by inhibiting the acetylcholinesterase (AChE). Still, their limited efficacy has prompted researchers to develop new ChEIs that could also reduce the oxidative stress by exhibiting antioxidant properties and by chelating the main metals involved in the disease. Recently, we developed some derivatives constituted by a 2-amino-pyrimidine or a 2-amino-pyridine moiety connected to various aromatic groups by a flexible amino-alkyl linker as new dual inhibitors of AChE and butyrylcholinesterase (BChE). Following our previous studies, in this work we explored the role of the flexible linker by replacing the amino group with an amide or a carbamic group. The most potent compounds showed higher selectivity against BChE in respect to AChE, proving also to possess a weak anti-aggregating activity toward Aβ42 and tau and to be able to chelate Cu2+ and Fe3+ ions. Molecular docking and molecular dynamic studies proposed possible binding modes with the enzymes. It is noteworthy that these compounds were predicted as BBB-permeable and showed low cytotoxicity on the human brain cell line.